Análise semiótica das propostas de redação do ENEM (2009-2015) - Azevedo Junior, José Bernardo de (2017)
This research aims to investigate how the Ministry of Education works with the mechanisms of syncretic enunciation of all the totality of meanings of the proposal of writing the Exame Nacional do Ensino Médio (ENEM) in the choice of texts of different languages, identified in the test as motivational texts. It also seeks to understand how the discursive interactions are given and what they establish to construct the production of meanings for the candidate. Created in 1998, the ENEM is a national level test and the initial objective was to evaluate the student at the end of basic education. As of 2009, when it gained greater popularity, the test to be used as a mode of selection in higher education institutions. The problematic is how the MEC articulates a perspective on a given theme, concretizing in texts of several languages for the candidate to understand them and, thus, to construct the argumentative e dissertation writing according to the competences required by the Exam. In order to respond to this questioning we work with the hypotheses that the MEC operates in the interaction regimes by combining procedures of the programming and manipulation regimes, structured by the choices of the enunciative strategies, to lead the candidate to adhere to the same point of view of the autarchy. These productions start from a themes introduced by the MEC with questions in the life of the candidate, which leads to test the hypothesis that the way to put the motivational texts in articulation, made available in several languages, forms the strategy of global enunciation with the sense of own point of view. The research also investigated whether there is a prominence in the plastic arrangement of the expression plane, which directs the candidate's thoughts with arguments that should be presented in his writing. The corpus of the research is composed of seven tests from the years 2009 to 2015. The analysis is based on the theoretical and methodological framework of the Discursive Semiotics of Algirdas Julien Greimas are explored the Sociosemiotics of Eric Landowski and the syncretism studies developed by Ana Claudia de Oliveira . For the understanding of the enunciation processes, the studies of José Luiz Fiorin, Norma Discini and Diana Barros are prioritized, as well as official government documents related to Education